De lingua Latina deque spiritualitate Benedictina fundamentis Europae - Albert, Sigrides (Nordlit, 2014)
Latin and Benedictine spirituality: Foundations of Europe. Europe has many shared roots. Among these roots both the Latin language and the spirituality of Saint Benedict are of importance. This article discusses how this came to pass and illustrates the kind of impact the Latin language and the spirituality of Saint Benedict has had on our culture. In dealing with these subject matters the author outlines several significant historical circumstances. Finally, there is a brief discussion regarding what conclusions that should be drawn and how these might serve as inspiration for us today.